Stepwise low concentration atropine for myopic control: a 10-year cohort study - Meng-Ni Chuang (Nature Portfolio, 2021)
Abstract The aim of this study was to analyze changes in refraction and evaluate the variables in school children who received atropine as myopic control for 10 years. Low-concentration atropine (0.05%) was prescribed initially, and the dose was increased in a stepwise manner if rapid myopic progression (≥ 0.5D per half year) was noted during the regular follow-up visit. 23 children with a mean age of 6.96 ± 1.07 years were included. The initial spherical equivalent was − 1.25 ± 0.84 D. The overall mean myopic progression was − 0.30 ± 0.27 D/year. Younger initial age, female, higher initial spherical equivalent and the need of higher concentration of atropine were found to be risk factors for myopic progression in multivariate mixed-effect analysis (p = 0.013, 0.017, 0.024 and 0.014). Children who kept using a lower concentration of atropine (≤ 0.1%) tended to have slower myopic progression throughout the 10-year course than those who shifted to higher concentrations (> 0.1%) (p ≤ 0.001). Stepwise low concentration of atropine might be effective for long-term myopic control in school students. Those who had poor response to lower concentration of atropine may have the risk of faster progression, even with high concentration of atropine. Additional or alternative treatment might be considered.